Comparative Evaluation of Trueness of Dental Impressions Using Digital Scanners: An In vitro Study - Ch Bindhu Sree; Pradeep Koka; I Kavya Sri; Jisa A. Alex; K Deepa Rani; V. Bhanu Chander (Journal of Pharmacy and Bioallied Sciences)
Aim: This study aims to evaluate and compare the trueness of four commercially available digital scanners. Methodology: A prepared lower first molar in a typhodont model, featuring dimple markers at line angles, served as the reference. Caliper measurements of dimple distances provided the reference dataset. Four desktop scanners each performed 10 scans of the model. EXOCAD software was used to process the digital scans, generating study datasets. Scanner datasets were then compared to the caliper reference data to evaluate trueness. Results: Repeated measures analysis of variance (ANOVA) determined significant differences (P < 0.05) in buccolingual and mesiodistal trueness between four scanners. Descriptive statistics revealed the UP3D scanner was most accurate in the buccolingual direction, while both MEDIT and UP3D were most accurate mesiodistally. Conclusions: The Dentium rainbow scanner which was the only white light scanner in this study, showed less trueness than other types of scanners. The UP3D scanner which works on structured light principle had higher trueness.